MODERN PEDAGOGICAL TECHNOLOGIES IN DEVELOPING STUDENTS’ SPEAKING SKILLS IN ENGLISH LESSONS - Mo‘minova Sevinch, (TADQIQOTLAR, 2026)
ANNOTATION  This  article  examines  the  role  of  modern  pedagogical technologies  in  developing  students’  speaking  skills  in  English  lessons.  The  study highlights the importance of communicative competence in foreign language learning and  analyzes  effective  teaching  methods  that  encourage  active  participation  of students. Particular attention is given to interactive teaching methods, communicative language teaching, digital technologies, gamification, and project-based learning. The article  concludes  that  the  use  of  modern  pedagogical  technologies  significantly improves students’ motivation, confidence, and ability to communicate in English.